Early mortality in acute kidney failure: comparison between critically Ill and non-critically Ill patients - Guevara Tirado, Alberto (2026)
ABSTRACT Introduction: Acute kidney injury (AKI) carries high mortality during its early course, yet few studies compare outcomes between critically ill and non-critical patients. Materials and Methods: Multicenter study including 5,060 hospitalized adults with AKI. Early mortality was defined as death within the first 14 days. Clinical characteristics were compared between patients admitted and not admitted to the ICU using standard statistical tests and Cox regression models. Results: ICU patients showed greater hemodynamic and metabolic compromise, with higher mortality (24.4% vs. 6.2%). In adjusted models, age, sodium, and potassium were associated with increased risk of early mortality, whereas bicarbonate and chloride showed inverse associations. Oxygen saturation and respiratory rate were also linked to poorer outcomes. Conclusions: Early mortality in AKI is influenced by electrolyte and hemodynamic disturbances, particularly among critically ill patients. Early identification of these abnormalities may enhance risk stratification and guide timely therapeutic decision-making.